With Joffre at Verdun: A Story of the Western Front - Brereton, F. S. (Frederick Sadleir), 1872-1957; Webb, Archibald, 1887-1944 (Salt Lake City, UT : Project Gutenberg, 2009)
"With Joffre at Verdun: A Story of the Western Front" by F. S. Brereton is a historical novel written in the early 20th century, likely during or shortly after World War I. The narrative primarily follows the experiences of Henri de Farquissaire and his friend Jules Epain, who find themselves interned in Ruhleben, a camp in Berlin, at the outbreak of the war. The book delves into themes of identity, peril, and the dire circumstances faced by prisoners navigating their way through the chaos of wartime Europe. The opening of the story introduces Henri and Jules as they navigate the streets of Berlin shortly after war is declared. They are arrested by a German constable and taken to a police station due to their French nationality and perceived threat as spies. Following their imprisonment, they are moved to the Ruhleben racecourse, where they struggle with harsh living conditions and contemplate escape. Henri, ever hopeful, suggests that there have been stories of successful escapes, setting the stage for their eventual plan to break free. The beginning not only establishes the central characters and their plight but also paints a vivid picture of the societal tensions prevailing at the onset of the Great War. (This is an automatically generated summary.)
Release date is 2009-12-28
Produced by Al Haines
Keywords: World War, 1914-1918 -- Fiction